The Dangers of History: Another Culture of Violence in Benue and Plateau States, Central Nigeria - Samaila Suleiman (Práticas da História)
How do competing historical narratives authorize or sanction violence? The central argument of this article is that the mobilization of historical narratives, whether popular, amateur or academic history, constitutes another form of violence that is far from the concerns of students of conflict in Central Nigeria. Based on oral interviews and a critical study of reports of government commissions, ethnic memoranda and propaganda leaflets, collected during fieldwork in Benue and Plateau states, Central Nigeria, the article examines the ways in which the extra-textual and meaning-assigning agency of history is weaponized as an instrument of negotiation and political violence. The article examines the various discourses around the Sokoto Jihad and the history wars among competing ethnic groups in Benue and Plateau states. The study is located within critical work that is attuned to the salience of symbolism in understanding the capacity of vengeful historical discourses to inflame violence.